Differentially regulated induced resistance marker enzymes in soybean genotypes resistant and susceptible to Asian soybean rust - Almeida, Hebréia Oliveira; Barbosa, Meire de Oliveira; Marques, Ana Ermelinda; Pereira, Tânus Henrique Abdalla; Magalhães Júnior, Marcos Jorge; Tessarollo, Nayara Gusmão; Games, Patrícia Dias; Barros, Everaldo Gonçalves de; Stolf-Moreira, Renata; Marcelino-Guimarães, Francismar Corrêa; et al. (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate induced resistance to Asian soybean rust by means of enzyme activities in soybean genotypes contrasting as to their susceptibility to Phakopsora pachyrhizi. Total protein and the activities of five induced resistance marker enzymes (lipoxygenases, peroxidases, phenylalanine ammonia‑lyase, chitinases and β‑1,3‑glucanases) were evaluated in leaf extracts of soybean plants of the genotypes Embrapa 48 (susceptible) and PI 561356 (resistant), inoculated or not with the pathogen. Discrepant defense responses were obtained between the two genotypes and among the leaf harvest times (12, 72, and 168 hours after inoculation). The induction response of these enzymes resembles the biphasic defense in Embrapa 48 and is consistent with that observed in other pathological systems. However, the genotype PI 561356 responded with a decrease in total protein concentration and in enzymatic activities, indicating a general reduction in the metabolism of the infected plants. There is an important mechanism of resistance for the genotype PI 561356, not yet reported, which is grounded on the metabolic ways involving these induced resistance marker enzymes and on the mechanisms that use lower concentrations of total protein, such as the ones with metabolic pathways in response cascade.